Analisis Kinerja Protokol Routing AODV, DSR, dan OLSR pada Mobile Ad hoc Network Berdasarkan Parameter Quality of Service - Alamsyah Zakaria; Eko Setijadi; I Ketut Eddy Purnama; Mauridhi Hery Purnomo (Universitas Syiah Kuala, 2018)
MANET is autonomous, self-configured, and applicable to emergency locations such as forest fires, earthquakes, floods, and health monitoring. However, challenges and difficulties faced by the mobile ad-hoc network (MANET) is a dynamically built network system, without the support of infrastructure in communicating between one node and other nodes, and limited energy sources. To overcome MANET problems and to obtain optimal network quality, the selections of routing protocols and quality of service (QoS) are significant in MANET design. This study aims to analyze the performance of routing protocols: dynamic source routing (DSR), ad-hoc on demand distance vector (AODV) and optimized link state routing (OLSR) based on QoS. The analyzed QoS parameters include packet delivery ratio (PDR), packet loss, throughput, and delay. Simulation results using network simulator version based on the number of node densities indicate that OLSR has better performance compared to AODV and DSR regarding PDR, packet loss, throughput, and delay.